Review: Understanding Rare Genetic Diseases in Low Resource Regions Like Jammu and Kashmir – India - Angural, Arshia; Spolia, Akshi; Mahajan, Ankit; Verma, Vijeshwar; Sharma, Ankush; Kumar, Parvinder; Dhar, Manoj Kumar; Pandita, Kamal Kishore; Rai, Ekta; Sharma, Swarkar (Frontiers in Genetics, 2020)
Rare diseases are the clinical conditions affecting a few percentage of individuals in a general population compared to other diseases. Limited clinical information and a lack of reliable epidemiological data make their timely diagnosis and therapeutic management difficult. Emerging Next-Generation DNA Sequencing technologies have enhanced our horizons on patho-physiological understanding of many of the rare diseases and ushered us into an era of diagnostic and therapeutic research related to this ignored health challenge. Unfortunately, relevant research is meager in developing countries which lack a reliable estimate of the exact burden of most of the rare diseases. India is to be considered as the “Pandora’s Box of genetic disorders”. Owing to its huge population heterogeneity and high inbreeding or endogamy rates, the literature indicates endogamy highly detrimental to health as it enhances the degree of homozygosity of recessive alleles in the general population, a higher burden of rare recessive genetic diseases is expected. The population of a low resource region Jammu and Kashmir – India, is highly inbred. Some of its population groups variably practice consanguinity. In context with the region’s typical geographical topography, highly inbred population structure and unique but heterogeneous gene pool, a huge burden of known and uncharacterized genetic disorders is expected. Unfortunately, many suspected cases of genetic disorders remain undiagnosed or misdiagnosed due to lack of appropriate clinical as well as diagnostic resources in the region, causing patients to face a huge psycho-socio-economic crisis and many a time suffer life-long with their ailment. In this review, the major challenges associated with rare diseases are highlighted in general and an account on the methods that can be adopted for conducting fruitful molecular genetic studies in genetically vulnerable and low resource regions is also provided, with an example of a region like Jammu and Kashmir – India.